Brief Review of Right Aortic Arch with Aberrant Left Subclavian Artery - Oztas, Didem Melis; Umutlu, Muzaffer; Ertan, Melike; Beyaz, Metin Onur; Badem, Serdar; Erdinc, Ibrahim; Ulukan, Mustafa Ozer; Unal, Orcun; Conkbayir, Cenk; Alpagut, Ufuk; Ugurlucan, Murat (AORTA, 2019)
Development anomalies of the aortic arch and its major branches are rare congenital cardiovascular disorders. In this article, we present aberrant left subclavian artery associated with right aortic arch.
Keywords: subclavian artery; aberrant; aortic arch